Η ενετική μονή Santa Maria dei Miracoli Χανίων: τεκμηρίωση, ιστορικές φάσεις και μελέτη ανάδειξης - Δεληγιάννη, Ελένη Όλγα (Σχολή Αρχιτεκτόνων Μηχανικών, 2013)
The Venetian monastery of Santa Maria dei Miracoli, on the hill Kastelli, is of the six Latin monasteries that existed in Chania and is one of the unique monuments of the Venetian period that integrates structures directly related to the historical development of the city. Nowadays, the monastery is preserved in ruins as major part the katholikon is destroyed, except the southern wall with its three blind apses, the southeast corner of the sanctuary and part of the pointed arch, at a height just above the genesis. Part of the cloister and its surrounding arcades are also preserved. The eastern side of the monument is based on the Byzantine wall and becomes immediately apparent to the visitor from the port. Despite the location of the monument and its proximity to a number of historical buildings, longtime neglect, incompatible interventions, the protection regime and the depreciation of the monument from residents degrade its cultural and architectural significance and make it hardly recognisable inside the urban fabric. The monument’s surveying, along with a thorough study of its history, clarified the complexities of its historic phases and led to prototype conclusions about its evolution in time. Among these and perhaps the most important of all, is establishing the existence of a three-aisled basilica of the early years of Venetian rule, which was not mentioned in previous studies.